The Influence of Corporate Culture and Compensation on Employees Commitment: The Role Of Satisfaction Work As Variables Intervening - Fakhruddin Siregar; Zulkifl Musannip Efendi Siregar; Nurintan Asyiah Siregar; Sumitro Sumitro; Hayanuddin Safri (Garuda Prestasi Nusantara Consulting, 2023)
This research aims to analyze the influence of company culture and compensation To Commitment Work Dano Permai Housing Employees: The Role of Satisfaction Work As Variable Intervening . This type of research is quantitative research and the respondents for this research as a sample are Dano Permai Housing in Labuhanbatu Regency with 40 employees . The data analysis method uses Partial Least Square (PLS) with smartPLS software . Research shows that company culture has a positive effect on employee work commitment , compensation has a positive effect on employee work commitment , company culture and compensation have a positive effect on employee work commitment through job satisfaction as an intervening variable Keywords: Company Culture, Compensation, Work Commitment, Job Satisfaction